Factors that Influence the Decision to Purchase Spotify Premium Services - Putri Windy Aprilia; Wenti Krisnawati (Jurnal Manajemen Sains dan Organisasi, 2023)
Objective - The aim of the researcher is to determine the factors that influence the decision to purchase Spotify Premium services. Design/Methodology/Approach - Researchers used a quantitative approach, collecting data using questionnaires among 100 respondents who were or had used Spotify premium at Muhammadiyah University Gresik. The analysis technique used was purposive sampling with the help of software, namely SPSS 24. Research Findings - From the results of the researchers' tests, it was found that visual merchandising had a positive but not significant effect, advertising creativity had a positive and significant effect, e-service quality had a positive but not significant effect, and perceived value had a positive and significant effect. Conclusions and Implications - Advertising creativity and perceived value have a significant positive effect on purchasing decisions for Spotify Premium services. Meanwhile, visual merchandising and e-service quality have no effect. So, to increase purchases of premium Spotify services, Spotify can increase advertising creativity and perceived value, especially for the target market of Muhammadiyah Gresik University students.